(untitled) (Conferencea, 2024)
This article looks at the analysis of the image of Meursault and the image of the hero in the novel “The Stranger” by Albert Camus, one of the bright representatives of modern literature, a famous writer of French literature, philosopher, journalist, creator whose works have caused great controversy among readers.